2017
DOI: 10.1038/s41467-017-00691-5
|View full text |Cite|
|
Sign up to set email alerts
|

Interlayer excitons in a bulk van der Waals semiconductor

Abstract: Bound electron–hole pairs called excitons govern the electronic and optical response of many organic and inorganic semiconductors. Excitons with spatially displaced wave functions of electrons and holes (interlayer excitons) are important for Bose–Einstein condensation, superfluidity, dissipationless current flow, and the light-induced exciton spin Hall effect. Here we report on the discovery of interlayer excitons in a bulk van der Waals semiconductor. They form due to strong localization and spin-valley coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
118
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(130 citation statements)
references
References 30 publications
(37 reference statements)
10
118
2
Order By: Relevance
“…3 and 6), are assigned to the pair of intra-(X A ) and interlayer (X ′ A ) A-excitons, and to the analogous pair of intra-(X B ) and interlayer (X ′ B ) Bexcitons. We use the signs and magnitude of the exciton g-factors as fingerprints the intra-and interlayer nature of the X A -and X ′ A -excitons respectively [39]. Namely, we conclude that g XA ≈ −4, while g X ′ A ≈ 8.…”
Section: Absorption Resonances In Mos2 Multilayersmentioning
confidence: 91%
“…3 and 6), are assigned to the pair of intra-(X A ) and interlayer (X ′ A ) A-excitons, and to the analogous pair of intra-(X B ) and interlayer (X ′ B ) Bexcitons. We use the signs and magnitude of the exciton g-factors as fingerprints the intra-and interlayer nature of the X A -and X ′ A -excitons respectively [39]. Namely, we conclude that g XA ≈ −4, while g X ′ A ≈ 8.…”
Section: Absorption Resonances In Mos2 Multilayersmentioning
confidence: 91%
“…For instance, the A* feature, which is ≈ 50 meV above the A transition, has been either assigned to excited excitonic states [10,11] or direct transitions at the H k-point [12][13][14]. More recently magneto-reflectance measurements showed that such feature could be attributed to an interlayer excitonic transition [15,16]. Hence it is desirable to further investigate the excitonic features present in MX 2 to better understand the effect of the SOC on the electronic band structure.…”
Section: Introductionmentioning
confidence: 99%
“…The near-K -point bands have a flat dispersion along the K − H axis, indicating that even in a multilayer structure, the corresponding quasi-particles are strongly confined within the individual layers and can be considered as effectively two-dimensional. Indeed, recent theoretical and experimental studies attribute the excitonic series in TMDC multilayer systems as being due to quasi twodimensional intra-and interlayer excitons [2,3].…”
Section: Introductionmentioning
confidence: 99%